2004
DOI: 10.4028/www.scientific.net/kem.264-268.2481
|View full text |Cite
|
Sign up to set email alerts
|

Steel Slag and Waste Management

Abstract: Steel slag is a waste material produced during the process of steel making. For many years, a large amount of steel slag has been deposited in slag storing yards, occupied farmland, silted rivers and polluted the environment. Many steel plants in the world have already taken up innovative waste recycling technologies with the ultimate objective of 100% recycling. The comprehensive utilization of steel slag is important for environmental protection and resource reuse in Turkey and abroad. It is clear that steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…They were classified as 25-40 mm, 19-25 mm, 5-19 mm and smaller than 5 mm. The chemical analysis and physical properties such as resistance to water action, to weathering, to abrasion, flatness index, specific gravity and water absorption of these slags were given in other paper of authors in this congress [4] and it was concluded that above mentioned steel slags satisfies the requirements to be used as an aggregate in asphaltic mixtures. The grading of steel slags was done by running the material through a series of sieves with progressively smaller opening and weighing the material retained on each sieve.…”
Section: Methodsmentioning
confidence: 99%
“…They were classified as 25-40 mm, 19-25 mm, 5-19 mm and smaller than 5 mm. The chemical analysis and physical properties such as resistance to water action, to weathering, to abrasion, flatness index, specific gravity and water absorption of these slags were given in other paper of authors in this congress [4] and it was concluded that above mentioned steel slags satisfies the requirements to be used as an aggregate in asphaltic mixtures. The grading of steel slags was done by running the material through a series of sieves with progressively smaller opening and weighing the material retained on each sieve.…”
Section: Methodsmentioning
confidence: 99%
“…During steel production, all unwanted elements and impurities are expelled as "slag" to guarantee maximum iron recovery (Government of India-Ministry of Steel, 2019). Steel slag waste has for many years been deposited in slag storage yards, farmlands, and surface water streams (Günay et al, 2004).…”
Section: Steel Slagmentioning
confidence: 99%